Labour market integration of international protection applicants in Ireland - Michał Polakowski; Emily Cunniffe (The Economic and Social Research Institute (ESRI), 2023)
In mid-2018, international protection applicants were granted permission to access the labour market in Ireland. This followed a landmark Supreme Court ruling in NHV v. the Minister for Justice and Equality, which overturned the prohibition on work for applicants. Between mid-2018 and the end of 2022, 12,180 first-time permissions for labour market access were granted to international protection applicants in Ireland. The granting of access to the labour market marked a significant change in how Ireland provides reception to applicants. This study examines the integration of international protection applicants into the labour market in Ireland over the past five years (2017-2022). It assesses how such access has been implemented, the key policy debates, the legal framework, good practices and the ongoing challenges to integration. Currently, an international protection applicant can apply for labour market access six months after lodging an application, as long as a first-instance recommendation has not been made on their application and the delay cannot be attributed to the applicant. If their application is approved, the applicant is issued with a labour market access permission. This is valid for 12 months and can be renewed as long as a final decision has not been taken on the applicant's international protection application. An applicant can enter employment or be self-employed, and these are not regulated differently. In terms of sectoral restrictions, while international protection applicants can work in most sectors, they cannot work in sectors that are public bodies, including the civil service, or in some cases, bodies primarily funded by public funding.
Keywords: 330; Arbeitsmarktintegration; Flüchtlinge; Arbeitsmarktpolitik; Irland